Mowy o poście Bazylego Wielkiego w łacińskiej wersji Rufina z Akwilei - Budzanowska-Weglenda, Dominika Łucja (Vox Patrum, 2020)
Fast has been known for centuries, both in the Greco-Roman world and in the ancient Orient. The Church Fathers emphasized the intrinsic value of fasting, criticizing the omission of the spiritual and moral element of this practice. Their treatises on fasting show the reliance of authors on one another, because they read their predecessors, repeated their ideas, but also presented the topic of fasting in their own way. This is very clear when we analyze the speeches of Basil the Great and Rufinus of Aquileia. Rufinus wrote his speeches under the clear influence of Basil’s homilies. The former not only translated Basil’s two homilies on fasting, but also interpreted them. The Latin text often shows that Rufinus develops some threads from Basil’s Greek texts significantly while omitting some. Both Basil and Rufinus focus on the moral and spiritual attitude of the fasting person and emphasize the spiritual and bodily benefits of fasting for the person involved and the surroundings. They call for abstinence from alcohol and for sexual purity.